More bang for the buck: media freedom and organizational strategies in the agenda-setting of human rights groups - Grömping, Max (Political communication, 2019)
Studies investigating the agenda-setting of human rights groups disagree on both their prospects of garnering political attention, and the factors that help them in that quest. This study makes the argument that we need to take account of both macro-institutional opportunity structures and actor-level strategies in order to gain a more complete understanding of the group-media interface. Specifically, it posits that the urgency of social problems only drives media attention toward groups if a country’s media landscape is sufficiently free, and that within these institutional constraints, groups themselves can enhance their media access by providing newsmakers with information subsidies. These claims are substantiated by way of a novel cross-nationally comparative data set of more than 1,000 domestic election monitoring and advocacy organizations. Findings show that media attention is structurally limited by the degree to which the news media serve as an open arena, and that even in countries with a free press, few groups achieve media access. At the same time, the most successful groups are not necessarily the most resourceful ones. Rather, strategic choices to invest in media effort, narrow policy engagement, and professionalization substitute for scarce resources, thereby giving groups “more bang for their buck.” The results clarify the causal mechanisms behind the dominance of resource-rich groups on the media agenda and reinforce calls for more globally comparative research into media agenda-setting.
Gesehen am 04.12.2019